Effect of thermotherapy on emergence and vegetative characteristics of genotypes of garlic - Velásquez-Valle, Rodolfo; Reveles-Hernández, Manuel (Revista Mexicana de Ciencias Agrícolas, 2019)
About 45% of the Mexican production of garlic is obtained in Zacatecas. Viral diseases of garlic can be transmitted by seed, thermotherapy has been used to reduce the viral concentration in garlic cloves; however, there is scarce local information about the impact of its impact on characteristics of plants originated from heat-treated bulbs; the purpose of this work was to determine the effect of heat treatment on the emergence and vegetative characteristics of 22 garlic genotypes. The garlic bulbs were preserved at 33 °C ±1 for six consecutive weeks. At the end of that period they were planted in the field. The emergence, height, neck diameter and number of leaves were recorded. The effect of the thermotherapy did not show a solid tendency, plants of seven heat-treated genotypes showed higher emergence and height values than those of their controls, while plants of only three and two genotypes from heat-treated bulbs had values of number of leaves and diameter of neck superior to those of their witnesses.